2014
DOI: 10.2215/cjn.10010913
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric G-Tail Length and Hospitalization for Cardiovascular Events in Hemodialysis Patients

Abstract: Background and objectives Telomeric G-tails play a pivotal role in maintaining the intramolecular loop structure of telomeres. Previous in vitro studies have suggested that the erosion of telomeric G-tails triggers cellular senescence, leading to organ dysfunction and atherosclerosis. The authors recently established a method to measure telomeric G-tail length using a hybridization protection assay. Using this method, this study investigated whether telomeric G-tail length could be used as a novel predictor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…This different distribution might indicate that telomere G-tail length is more strongly influenced by cardiovascular risk factors than is total telomere length. Recently, Hirashio et al reported that shorter telomere G-tail length was associated with future cardiovascular risk in hemodialysis patients, but that total telomere length did not predict cardiovascular events ( Hirashio et al, 2014 ). In addition, our study demonstrated that telomere G-tail length is significantly correlated with endothelial function and the severity of ARWMCs after adjustment for age, sex and baseline characteristics, although the association between total telomere length and these factors was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This different distribution might indicate that telomere G-tail length is more strongly influenced by cardiovascular risk factors than is total telomere length. Recently, Hirashio et al reported that shorter telomere G-tail length was associated with future cardiovascular risk in hemodialysis patients, but that total telomere length did not predict cardiovascular events ( Hirashio et al, 2014 ). In addition, our study demonstrated that telomere G-tail length is significantly correlated with endothelial function and the severity of ARWMCs after adjustment for age, sex and baseline characteristics, although the association between total telomere length and these factors was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this issue, we previously developed a telomere G-tail HPA method ( Tahara et al, 2005 ) which has the advantages of simple use, accuracy, and high sensitivity for G-tails in vitro. Additionally, recently we developed high-throughput automated machine for G-tail telomere HPA that is applicable for clinical use ( Hirashio et al, 2014 ). Telomere G-tail HPA methods might therefore be more suitable for clinical use than other G-tail length assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation is common in uremic patients, and we recently demonstrated that reduced TL is associated with inflammatory markers in uremic Caucasian hemodialysis (HD) patients [13] . Moreover, it was reported that a longer telomeric G-tail, that may be important to keep telomere function, was associated with a decreased risk of CVD in Japanese HD patients [14] . The mechanisms whereby these adverse conditions affect telomere biology are unknown and are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, G-tail length could fluctuate upon exposure to various stresses. Indeed, G-tail is also shortened in hemodialysis patients ( Hirashio et al, 2014 ). Mechanistically, factors that could modulate G-tail length include telomerase-mediated G-strand extension, end resection of the antisense C-strand, formation and resolution of higher-order structure called G-quadruplexes, loading of the shelterin protein complexes and innate hypersensitivity to oxidative stress.…”
mentioning
confidence: 99%